Blockade of IL-18Rα-mediated signaling pathway exacerbates neutrophil infiltration in imiquimod-induced psoriasis murine model - Akazawa, Hiroki; Nozaki, Yuji; Yamazawa, Hirotaka; Ishimura, Kaori; Ashida, Chisato; Okada, Akinori; Kinoshita, Koji; Matsumura, Itaru (Frontiers in Medicine, 2023)
Psoriasis is an immune-mediated inflammatory disease of the skin, which is characterized by epidermal hyperkeratosis and neutrophil infiltration. The interleukin (IL)-17/IL-23 pathway and associated cytokines play major roles in the pathogenesis and exacerbation of psoriasis. The IL-18/IL-18 receptor (R) α signaling pathway is important for Th1 cytokine production and differentiation of Th1 cells; however, its role in the pathogenesis of psoriasis remains unknown. In this study, we investigated the effect of the IL-18Rα-mediated signaling pathway in the pathogenesis of psoriasis in Il18ra-deficient mice (Il18ra -/-) and wild-type imiquimod (IMQ)-induced psoriatic dermatitis model mice. Blocking this pathway exacerbated IMQ-induced psoriatic skin inflammation. Il18ra deficiency led to significant increases in the levels of IL-1β, IL-6, IL-8, IL-17A, IL-23, and chemokine (C-X-C motif) ligand 2 in skin lesions. Gr1-positive cells highly infiltrated psoriatic skin lesions in Il18ra -/-mice compared to those in wild-type mice. Citrullinated histone H3-positive area was relatively broad in Il18ra -/-mice. These results suggest that IL-18Rα-mediated signaling pathways may inhibit psoriatic skin inflammation by regulating infiltration and activation of neutrophil and other innate immune cells.